Risk Factors Associated with Vancomycin-Resistant Enterococcus in Intensive Care Unit Settings in Saudi Arabia - Shorman, Mahmoud; Al-Tawfiq, Jaffar A. (Interdisciplinary Perspectives on Infectious Diseases, 2013)
Background. Vancomycin-resistant enterococci (VRE) are significant nosocomial pathogens worldwide. There is one report about the epidemiology of VRE in Saudi Arabia. Objective. To determine the risk factors associated with VRE infection or colonization in intensive care unit (ICU) settings. Design. This is a descriptive, epidemiologic hospital-based case-control study of patients with VRE from February 2006 to March 2010 in ICU in a tertiary hospital in Saudi Arabia. Methods. Data were collected from hospital records of patients with VRE. The main outcome measure was the adjusted odds ratio estimates of potential risk factors for VRE. Results. Factors associated with VRE included ICU admission for multiorgan failure, chronic renal failure, prior use of antimicrobial agents in the past three months and before ICU admission, gastrointestinal oral contrast procedure, and hemodialysis. Being located in a high risk room (roommate of patients colonized or infected with VRE) was found to be protective. Conclusions. Factors associated with VRE acquisition are often complex and may be confounded by local variables.